The Optimal Lipid Chain Length of a Membrane-Permeabilizing Lipopeptide Results From the Balance of Membrane Partitioning and Local Damage - Steigenberger, Jessica; Verleysen, Yentl; Geudens, Niels; Martins, José C.; Heerklotz, Heiko (Frontiers in Microbiology, 2021)
Pseudodesmin A (PSD) is a cyclic lipodepsipeptide produced by Pseudomonas that kills certain bacteria at MIC1/2 in the single micromolar range, probably by permeabilizing their cellular membranes. Synthetic PSD variants where the native decanoic (C10) acyl chain is varied in length from C4 to C8 and C12 to C14 carbons were described to be not or less active against a panel of gram-positive strains, as compared to native PSD-C10. Here, we test the membrane-permeabilizing activity of PSD-C4 through PSD-C14 in terms of calcein release from liposomes, which is characterized in detail by the fluorescence-lifetime based leakage assay. Antagonistic concentrations and their chain length dependence agree well for liposome leakage and antimicrobial activity. The optimal chain length is governed by a balance between membrane partitioning (favoring longer chains) and the local perturbation or “damage” inflicted by a membrane-bound molecule (weakening for longer chains). Local perturbation, in turn, may involve at least two modes of action. Asymmetry stress between outer and inner leaflet builds up as the lipopeptides enter the outer leaflet and when it reaches a system-specific stability threshold, it causes a transient membrane failure that allows for the flip of some molecules from the outer to the inner leaflet. This cracking-in may be accompanied by transient, incomplete leakage from the aqueous cores of the liposomes observed, typically, for some seconds or less. The mismatch of the lipopeptide with the lipid leaflet geometry, expressed for example in terms of a spontaneous curvature, has two effects. First, it affects the threshold for transient leakage as described. Second, it controls the rate of equilibrium leakage proceeding as the lipopeptide has reached sufficient local concentrations in both leaflets to form quasi-toroidal defects or pores. Both modes of action, transient and equilibrium leakage, synergize for intermediate chain lengths such as the native, PSD-C10. These mechanisms may also account for the reported chain-length dependent specificities of antibiotic action against the target bacteria.